Pilot study of Stem Cell Therapy in Heart Failure Patients - Zaman, M Mustafa; Khaled, Md Fakhrul Islam; Dey, Bishnu Pada; Begum, Masuda; Ahmed, Sayed Mainuddin; Islam, Md Azharul; Banerjee, Sajal Krishna; Hoque, Md Harisul (University Heart Journal, 2020)
Introduction: Chronic heart failure with reduced ejection fraction is a major complication of diseases involving myocardium. Despite numerous pharmacological interventions and invasive therapeutic techniques, therapeutic options for end stage heart failure remain limited to left ventricular assist device & organ transplantation. Regenerative medicine may bring hope here. Method: This pilot study was carried out at the Department of cardiology in collaboration with department of haematology, Bangabandhu Sheikh Mujib Medical University, Dhaka, from October 2017 to March 2018. Considering inclusion & exclusion crieteria ten (10) patients were taken in stem cell group and ten (10) patients in control group. Patients in the control arm received standard of care in accordance with practice guidelines for heart failure management (GDMT). Patients in the cell therapy arm received, in addition to standard of care, bone marrow–derived cardiopoietic stem cells (G-CSF) meeting quality release criteria. Baseline clinical and echocardiographic data were obtained and recorded in pre-formed data sheet. Close liaison was maintained with all patients and followed up after 30 days & after 3 months and for any complication. The absolute change in 6 MWD from baseline to 30 days, 3 months & 6 months improved significantly in the both groups. But significant improvement was found at 6 months follow up of 6MWD between the two groups (300±28 vs 375±25, p= 0.04). Baseline BORG scale was similar in the control group and the SCT group (8.1±0.56 and 8.3±0.67 respectively, P= 0.45). The absolute change in BORG scale from baseline to 30 days, 3 months & 6 months improved significantly in the both groups. But improvement was not statistically significant in between the two groups (p= 0.32, 0.45, 0.23 respectively). Echocardiographic observation also revealed a similar baseline LVIDd, LVEF level in the control group and the SCT group which was not statistically significant (p = 0.45, 0.52 respectively). Gradual improvement in LVIDd were found at 30 days, 3 months, 6 months follow up observation but statistically significant absolute change was found only at 6 months follow up in between groups (62.4±1.8 vs 56±2.4, p=0.03). Baseline LVEF were less than 30% in both control & SCT group (29.5±0.8% & 28.7±1.3% respectively). The echocardiographic evaluation also revealed a significant increase in LVEF at 6 months (34% ±1.6 and 40% ± 2.5%, p = 0.04) of follow-up in between group but not at 30 days & 3 months follow up. University Heart Journal Vol. 16, No. 2, Jul 2020; 52-58